El desarrollo económico e industrial a partir del ingenio de los agroproductores canarios en la sociedad larense, 1961-1981 (Agroindustria, Sociedad y Ambiente, 2018)
The objective of this research is to analyze the development and industrialization of the ingenuity of the Canarian agro-producers in the Larense society, during the historical period that covers from 1961 to 1981, since it is to recognize the participation of Canarian farmers in the economic, business, cultural and industrial development in the Lara state, with the purpose of assessing and preserving its material and immaterial legacy. The methodology of historical science was applied through the historical method, with the use of primary and secondary sources. The result was an understanding of the intercultural process experienced in the region, based on the syncretism carried out between immigrants and Venezuelans, obtaining the development of Larense society as a result of the economic and cultural dialogue from the multidisciplinary point of view that through the use of new techniques and technologies, a productive apparatus was developed in the Larense region, and nationally significant companies such as EL TUNAL, AGROISLEÑA and TANAUSU were founded, which have given an endless contribution to society from the economic, social and cultural. In conclusion, the relevant role of canaries in Larense society is well known, since the development of the horticultural culture, agricultural production and industrial construction is recognized as a legacy of that conviction of cultivation of different crops, which made short term were the daily consumer foods within the table of the Venezuelan.
Keywords: Economic and industrial development; Canarian immigrants; Larense society